Phenomenological Study off Student’s Communication Motives for Participating in the 2022 MBKM Program - Muhammad Bayuputra Danizar; Farida Hariyati; Diana Anggraeni (STABN RADEN WIJAYA WONOGIRI, 2023)
MBKM is a program from the Ministry of Education and Culture. This program aims to provide students with a platform to develop their talents, soft and hard skills, and the knowledge they have learned on campus. In taking action based on the motives that exist in the individual to get what he wants; we divide them into two (because of motives) and (in order to motives). With a phenomenological approach, this study uses qualitative methods with in-depth interviews with informants. This study aims to know “UHAMKA Students’ Communication Motives for Participating in the 2022 MBKM Program”. Research results suggest that a causal motive is a driving force behind students' decision to join the MBKM program. It is because the informants want to improve their communication skills and gain excellence from this program. Concerning the goal motive, the students expect to develop skills and benefits from the MBKM Program. The communication motives the students used are persuasive communication motives and interpersonal communication motives. The students have hopes to invite others to join the MBKM program, and they interpersonally communicate to find out information. It will establish the communication motives they convey.